Nurith Aviv 5 films, 1 livre = Lashon ḳodesh, śefat ḥol - Aviv, Nurith 1945- (Éd. Montparnasse, 2011)
Langue sacrée, langue parlée: Originally a sacred language of prayer and scripture, Hebrew has now become the spoken language of everyday life in Israel. Here thirteen artists and writers born in Israel attempt to describe their relationship to the religious dimensions of the Hebrew language